Analysis Endurance Profile (Vo2max) of Women's Volleyball Athletes: Yo-yo intermittent test level 1 - Rubiyatno; Supriatna, Eka; Suryadi, Didi; Haetami, Mimi; Firsta Yosika, Ghana (Indonesian Journal of Physical Education and Sport Science, 2023)
Study objectives . VO2max endurance is needed in volleyball, because this sport has the characteristics of jumping and shifting in various directions quickly. This study aims to determine endurance (VO2max) in female volleyball athletes at the Brojomusti club. Materials and methods. This research is a quantitative descriptive type using a survey method, in this research there are tests and measurements. The research instrument used the yo-yo intermittent recovery test level 1. The subjects in this study were female volleyball athletes at the Brojomusti club, totaling 15 athletes. Results. The results of the study obtained that there were athletes with a percentage of 26.7% in the less category, then 4 athletes in the moderate category with a percentage of 26.7% and there were 6 athletes in the good category with a percentage of 40%. Then there is 1 female athlete in the very good category with a percentage of 6.7%. Conclusion. Results This study shows that the women's volleyball athletes at the Brojomusti club are in the good category, but some athletes are still relatively low. With these results, it is hoped that they can provide an overview to the trainer so that they can provide training to increase the athlete's VO2max.